2018
DOI: 10.4103/ipj.ipj_82_15
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol, harmful use and dependence: Assessment using the WHO Alcohol Use Disorder Identification Test tool in a South Indian fishermen community

Abstract: Background: Fishermen have a high burden of alcohol-related morbidity. The Alcohol Use Disorder Identification Test (AUDIT) is used to classify individual to have harmful use of alcohol and probable alcohol dependence. Hence, this study was conducted among fishermen in a selected fishermen community in Puducherry, South India, to (a) assess the proportion of harmful alcohol use and probable dependence to alcohol among alcohol users using AUDIT tool and (b) find the sociodemographic factors associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…(Male fisherman, Sri Lanka #11) Bhondve, Mahajan, Sharma, and Kasbe (2013), in a study of Mumbai fishermen found that alcohol consumption was more common amongst fishermen who were stressed, with 31.8% blaming stress as the reason for alcohol use and 20.8% fishermen believing that alcohol increases work efficiency.…”
Section: Impli C Ati On S Of Find Ing S For Marine Re Source Governmentioning
confidence: 99%
“…(Male fisherman, Sri Lanka #11) Bhondve, Mahajan, Sharma, and Kasbe (2013), in a study of Mumbai fishermen found that alcohol consumption was more common amongst fishermen who were stressed, with 31.8% blaming stress as the reason for alcohol use and 20.8% fishermen believing that alcohol increases work efficiency.…”
Section: Impli C Ati On S Of Find Ing S For Marine Re Source Governmentioning
confidence: 99%
“…Four of the 13 studies were conducted in Morocco, 2 studies in India, 1 study each was investigated in France, Croatia, Greece, Denmark, the Seychelles and the Philippines and 1 study was carried out anonymously. Eight of the 13 studies were conducted among fishermen [5,6,8,[10][11][12][13][14] and 5 among seafarers [15][16][17][18][19].…”
Section: Characteristics and Methods Of Selected Articlesmentioning
confidence: 99%
“…Three [5,6,11] of the 13 studies investigated the consumption of alcohol among seafarers and fishermen as the main question (Table 1). Ten studies focused on a different question and surveyed alcohol consumption only as an accompanying parameter or risk factor.…”
Section: Characteristics and Methods Of Selected Articlesmentioning
confidence: 99%
See 2 more Smart Citations